(untitled) (Pedagogy of Higher and Secondary Education, 2002)
The application of system approach to training of the technical university students is esteemed. The hierarchic frame of the purposes and subpurposes like “Tree of purposes” as main “gear” of system approach implementation is offered. The "Tree of the purposes” - "Formation of system approach skills at studies of a physics course“ is adduced.